Occurrence and management of severe bleeding episodes in patients with hereditary factor X deficiency. Issue 4 (22nd May 2021) - Tarantino, Michael D.
Abstract: Vitamin K–dependent factor X (FX) plays an important role in thrombin formation, and a deficiency in FX can cause impaired coagulation, the severity of which is usually correlated with the degree of deficiency. Due to the critical role that FX plays in the coagulation cascade, FX deficiency is associated with a higher risk of bleeding than deficiencies in other coagulation factors. Patients with the hereditary autosomal‐recessive homozygous form of FX deficiency, which occurs in approximately 1:1, 000, 000 individuals worldwide, are often diagnosed when they present with spontaneous life‐threatening haemorrhage (most often intracranial haemorrhage) during the first month of life. In addition to central nervous system bleeds, other severe bleeding types experienced by such patients may include umbilical cord bleeding, gastrointestinal or pulmonary haemorrhage, intramuscular haematomas and/or haemarthrosis. Delayed treatment or inadequate replacement of FX may result in developmental delays, musculoskeletal disabilities or death. The high risk of recurrent severe bleeding necessitates prophylactic replacement therapy for many individuals with severe FX deficiency. Available products for replacement therapy include plasma‐derived FX concentrate and prothrombin complex concentrates. Fresh‐frozen plasma may be used when concentrates are not available but is a less efficient means of FX replacement. This article reviews the literature on severe bleeding in individuals with hereditary FX deficiency and discusses current treatment options.